Silent Songs of Kolbano : Messages And Meanings In Dawan Death Speech Tradition In South Pene Kolbano Subdistrict South Central Timor Regency: English - Sabuna, Fodita; Anabokay , Yanrini Martha; Isu, Rudolof Jibrael (Universitas Persatuan Guru 1945 NTT, 2025)
This study explores the